ChemInform Abstract: Eringiacetal A, 5, 6‐seco‐(5S, 6R, 7R, 9S)‐5, 6:5, 7:6, 9‐Triepoxyergosta‐8 (14), 22‐diene‐3β, 7β‐diol, an Unusual Ergostane Sterol from the Fruiting Bodies of Pleurotus eryngii. Issue 48 (December 2015) - Kikuchi, Takashi; Masumoto, Yuki; In, Yasuko; Tomoo, Koji; Yamada, Takeshi; Tanaka, Reiko
Abstract: The title compound is obtained as colorless crystals.